2020
DOI: 10.21608/jpp.2020.87104
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Productivity, Profitability and Land Use Efficiency by Relay Intercropping Watermelon with some Wheat Cultivars under Drip Irrigation System

Abstract: A field experiment was carried out in Ismailia Experiment Station, ARC, Ismailia Governorate, Egypt, during 2016/2017 and 2017/2018 seasons, to study the effect of planting dates (1 st , 10 th and20 th March) of watermelon relay intercropping with wheat and wheat cultivars (Misr 1, Gemmiza 11and Sakha 93) on productivity, land use efficiency and profitability per unit area. A split-plot design was used with three replications. Results indicated that growth, yield and its attributes of wheat were insignificant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Although, the intercropping treatment with the lowest income increased net return by 31.6 and 20.3% as compared to sole watermelon in the first and second seasons, respectively. This result is in line with most other field studies reported that intercropping watermelon increased grower's profitability (Miller and Greene, 2018;Abd Allah et al, 2020).…”
Section: Economic Evaluationsupporting
confidence: 92%
See 1 more Smart Citation
“…Although, the intercropping treatment with the lowest income increased net return by 31.6 and 20.3% as compared to sole watermelon in the first and second seasons, respectively. This result is in line with most other field studies reported that intercropping watermelon increased grower's profitability (Miller and Greene, 2018;Abd Allah et al, 2020).…”
Section: Economic Evaluationsupporting
confidence: 92%
“…Its cultivated area was 45,029 ha in the summer season (FAO, 2020), and about 90% of this area was in newly reclaimed land. Watermelon rows spacious allow for successful intercropping farming, which allows shares of land resources and production inputs as well as increased productivity, land use efficiency and farmer income (Huang et al, 2015;Miller and Greene, 2018;Abd Allah et al, 2020). Management of intercrops to reach maximum complementarity and minimum competition between both crops includes agriculture different decisions as population density and nutrients requirements, especially nitrogen.…”
Section: Introductionmentioning
confidence: 99%